Editorial: frontiers of sulfur metabolism in plant growth, development, and stress response - Kopriva, Stanislav; Talukdar, Dibyendu; Takahashi, Hideki; Hell, Rüdiger; Sirko, Agnieszka; D'Souza, Stanislaus F.; Talukdar, Tulika (Frontiers in plant science, 2016)
Editorial: Frontiers of Sulfur Metabolism in Plant Growth, Development, and Stress Response